Disproportional Control Rights and the Governance Role of Debt - Dey, Aiyesha; Nikolaev, Valeri; Wang, Xue (Management Science, 2016)
We examine the governance role of debt in the context of U.S.-based dual class ownership structures. We hypothesize that the use of debt alleviates the conflict between shareholder classes by balancing the power of controlling insiders. We document that dual class firms have higher leverage and a greater propensity to issue private debt; they also more frequently use cash sweeps and performance-based covenants. Dual class firms with greater agency conflicts and a greater need to access the capital market appear to rely more extensively on debt. These findings are consistent with controlling insiders bonding against the agency costs associated with dual class ownership. The governance role of debt is further corroborated by the valuation effect of debt for dual class companies. Private debt issuances trigger greater positive market reactions to the inferior dual class stock in relation to both the superior dual class stock and a matched sample of single class firms. Further, leverage attenuates the previously documented adverse effect of dual class status on Tobin’s q. Taken together, our analyses suggest that dual class firms use debt as a complementary governance mechanism. This paper was accepted by Mary Barth, accounting.